ANALYSIS OF FUNCTIONAL LEAF TRAIT VARIATION AMONG THE DOMINANT UNDERSTOREY SPECIES IN THE PINE FOREST OF MORNI HILLS, PANCHKULA, HARYANA. - Somveer Jakhar; Himanshi Dhiman; Harikesh Saharan (Journal of Tropical Life Science, 2021)
Functional diversity is an essential concept in the field of functional ecology. It refers to the relative abundance, range and value of the functional traits present in a given community or ecosystem. Plant functional traits (leaf traits, stem traits, root traits etc.) create a link between ecosystem processes and plant physiology, and thus offer a powerful means to study the global change on vegetation dynamics and ecosystem processes. When plant species grow in different environments, their physiological and functional traits get modify due to change in site specific conditions. In the present study, leaf functional traits (leaf size-LS, specific leaf area-SLA, leaf dry matter content-LDMC, leaf nitrogen content-LNC, leaf phosphorus content-LNC and leaf nitrogen to phosphorus ratio-N:P) of twelve dominant understorey species (6 shrubsÂ and 6 herbs) were examined in the Pine forest of Morni Hills range of lower Shivaliks, Haryana, India. During the study, the maximum value of leaf size was obtained for Murraya koenigii and Cynoglossum zeylanicum; while the maximum value of LDMC was obtained for Toxicodendron parviflorum and Dicliptera chinensis among shrubs and herbs respectively. Other than this, highest value of SLA, LPC and LNC were calculated for Parthenium hysterophorus among shrubs and Oxalis corniculata among herbs. The calculated values were also found to be significantly correlated among the selected plant species.